A COMPARATIVE REVIEW OF CONFERENCE MANAGEMENT SYSTEM (Journal of Technology and Operations Management, 2023)
This article provides a brief yet comprehensive review of Conference Management Systems (CMS), showcasing widely-used platforms such as EasyChair, ConfBay, OpenConf, Microsoft CMT, COMS, and EDAS—tools commonly employed by conference organizers. The strengths and features of each platform are explored, with a focus on key aspects such as paper submission, the review process, registration, agenda and program management, virtual conference support, proceedings, and email communication.  Through this comparative analysis, the diverse functionalities and distinctive contributions of each CMS become evident, offering valuable insights for conference organizers to make well-informed decisions tailored to their specific event requirements. For instance, EasyChair is recognized for its user-friendly interface and the inclusion of the Virtual Conference Support (VCS) feature, addressing the growing trend of virtual and hybrid events. ConfBay positions itself as a user-friendly CMS with customizable features, while OpenConf offers versatility through its Community, Plus, and Professional Editions. This review highlights the unique strengths of each CMS, empowering organizers with a deeper understanding of their capabilities. The adaptability of these systems to the evolving landscape of academic and scientific events is a central theme, underscoring their potential to significantly contribute to the success and efficiency of conferences globally. Ultimately, this analysis serves as a valuable resource for navigating the complex landscape of CMS platforms, guiding organizers toward optimal choices aligned with their unique event management needs.